«Tradiciones jacobeas en la Castilla del siglo XV: intertextualidades (de Vicente de Beauvais a Rodríguez de Almela)» - Fernández Gallardo, Luis (Revista de Literatura Medieval, 2016)
Resumen: Alonso de Cartagena, uno de los intelectuales castellanos más notables del siglo XV, jugó un papel decisivo en la difusión de las tradiciones relativas a la vida, martirio y «translatio» de Santiago. Utilizó a Vicente de Beauvais, en lugar de fuentes hispánicas. Su discípulo Rodríguez de Almela siguió a su maestro, añadiendo otras fuentes históricas. Ello es revelador de un empeño por afirmar la historicidad de las tradiciones de Santiago y, por tanto, de racionalizar la materia hagiográfica. Palabras clave: siglo XV, Santiago, Alonso de Cartagena, Diego Rodríguez de Almela, historiografía. «Jacobean Traditions in the Fifteenth Century Castile: Intertextualities (from Vincent de Beauvais to Rodríguez de Almela)» Abstract: Alonso of Cartagena, one of the most remarkable Castilian intellectuals of the fifteenth century, played a fundamental role in spreading the traditions concerning the life, martyrdom and «translatio» of Santiago. He used the information given by the historian Vincent de Beauvais, instead of Hispanic sources. His disciple Rodríguez de Almela followed him, but adding other historical sources. That is indicative of an effort to affirm the historicity of the traditions of Santiago and rationalize the hagiographic materials. Keywords: XVth Century, St James, Alonso de Cartagena, Diego Rodríguez de Almela, historiographic literature.